Dialectical thinking and health behaviors: The effects of theory of planned behavior. (16th April 2012) - Jiang, Feng; Lu, Su; Hou, Yubo; Yue, Xiaodong
<x xml:space="preserve">Abstract</x> The primary purpose of this study was to investigate whether the theory of planned behavior (TPB) mediated the relationship between dialectical thinking and health behaviors. A sample of 285 undergraduates was tested with a dialectical thinking styles scale, health promoting lifestyle profiles, and TPB questionnaires. Structural equation modeling was used for data analysis. Results indicated that all the three dimensions of thinking styles (belief in the connection, acceptance of change, and acceptance of contradiction) exerted significant effects on TPB constructs. Specifically, the connection and the change dimensions had positive effects on health behaviors mediated by TPB, whereas the contradiction dimension had a negative effect. Model 2 showed a satisfactory fit, demonstrating the influential pathways between dialectical thinking and health behaviors. Implications in issues of health promotion and future research are discussed.